Effects of imo-compost on growth of maize (Zea Mays L.) - Awing, Norida Hanim (2014)
Paddy husk (PH) and corn stalk (CS) residues are usually disposed through open burning. Compost could instead be produced from these residues. Composting is the conversion of organic residues into useful organic soil amendments that provide nutrients to crops and enhance the tilth, fertility, and productivity of soils. However, some composting methods are not effective in producing good quality compost. Therefore, this study was conducted to develop an effective way of utilising these residues by composting with indigenous microorganisms (IMO). Inoculated bacteria from steamed white rice (SWR), aerated fish pond water (AFPW), and kitchen wastes (KW) were used. Composting was conducted in a white polystyrene box measuring 30 x 15 x 25 cm and attained an ambient temperature of 25.8˚C for 34 days. The composts were analyzed for C/N and C/P ratios, pH (H2O and KCl), nutrient content, organic carbon, organic matter, ash, Cation Exchange Capacity (CEC), humic acid (HAs), acidic functional groups, E4/E6 ratio, spectral, and microbial count. IMO-composts were blackish in colour without foul odours which indicate the stable nature of the composts. IMOcompost from corn stalk residues using aerated fish pond water (AFPW) inoculants showed higher positive relationship of HA with total N, P, K, C/N and C/P ratio, pH, TOC, OM, and CEC compared to the other treatments. Identifying bacterial through FAME analysis for three different IMO sources, SWR, AFPW and KW showed the following five beneficial bacteria; Bacillus cereus from SWR, AFPW and KW, Bacillus sphaericus from KW, Bacillus megaterium from SWR, Acinetobacter calcoaceticus from KW and Microbacterium barkeri from AFPW. IMO-composts were further tested in a pot experiment (shelter rain house) whereby Sweet Corn (D56) variety of maize (Zea mays L.) was used as the test crop to evaluate the effect of IMOcompost on nutrient use efficiency by maize. The treatments evaluated were: (T0) no fertilization, (T1) N, P and K (4.84g urea + 2.48g muriate of potast (MOP) + 4.91g triple super phosphate (TSP)), (T2) 77.96g IMO(V)- compost(SWR-PH) + 0.72g MOP + 1.41g TSP, (T3) 74.54g IMO(V)- compost(SWR-CS) + 0.00g MOP + 0.64g TSP, (T4) 57.90g IMO(V)- compost(AFPW-PH) + 0.29g MOP + 2.35g TSP, (T5) 38.72g IMO(V)- compost(AFPW-CS) + 0.15g MOP + 2.48g TSP, (T6) 59.49g IMO(V)- compost(KW-PH) + 0.28g MOP + 2.32g TSP, and (T7) 51.41g IMO(V)- compost(KW-CS) + 0.04g MOP + 2.01g TSP. Application of chemical fertilizer was done on 10th and 28th day after sowing (DAS). Sandy clay loam Typic Tualemkuts (Bekenu Series) was used as the growth medium. The plants were harvested on the 50th day after sowing (DAS) during tassel stage. The plant parts (leaves, stems, and roots) were analyzed for N, P, and K and soil samples were analyzed for exchangeable K, Ca, Mg, and Na, CEC, organic matter, organic carbon, total N, available P and pH. Analysis of variance was used to detect treatment effect while Tukey’s test was used to compare treatment means. Application of IMO-compost affected soil pH, exchangeable cations, CEC, organic carbon, OM and available P compared to the control treatment (T0). The IMO-compost had no significant effect on total N. IMO-compost (steamed white rice (SWR) inoculants), (T3) had significant effect on dry weight production, while IMO-compost (aerated fish pond water (AFPW) inoculants), T5 had significant effect on N, P and K contents, their uptake, as well as their use efficiency by maize. This method was able to significantly reduce N, P and K application. It can be concluded that mature compost from corn stalk (CS) residue with aerated fish pond water (AFPW) inoculants contained more nutrients, high use efficiency by maize indicating it as a suitable organic soil amendment.